The Effectiveness of Using Distance Education During the Covid-19 Pandemic from Public Schools Students’ Perspectives in Jordan - Ababneh, Sana’; Maharmah, Hamza; Alkhresheh, Mutaz Mohammad; Alqatawneh, Safa’a Mohammad (Journal of Ecohumanism, 2024)
The current study set out to gain a better understanding of how public-school students felt about the efficacy of remote learning during the COVID-19 pandemic, and how those feelings varied according to gender. Using a descriptive survey approach, the study was implemented during the first half of 2020. In the Wadi el-seer Directorate of Education, all students enrolled in public schools made up the study population. The study sample included (334) students, (178) of whom were male and (156) of whom were female, selected using a simple random method. Here are the outcomes of the study: With an arithmetic average of 4.78, item (1) "Distance education works to enrich my education" rated top out of the items with a range of 3.60 to 4.78. "Distance education helped eliminate many student problems" (item 19) had the lowest mathematical average at (3.60) and was so rated last. In view of the recent Corona pandemic, the first question's analytical results showed that the schools in the Wadi el-Seer Directorate of instruction benefited greatly from remote instruction. Taken together, the sample's average perception was (4.30) and the field's standard deviation was (.558). The opinions of the sample participants about the overall tool averages do not alter according on the gender variable (males, females). National programs that advance the concept of distant education and strengthen collaboration between it with the Jordanian Ministry of Education should be supported, according to the experts.